Pre-service teachers’ emotional experience: Characteristics, dynamics and sources amid the teaching practicum - Ji, Yilong; Oubibi, Mohamed; Chen, Siyuan; Yin, Yuxin; Zhou, Yueliang (Frontiers in Psychology, 2022)
Recently, teacher emotions have become the focus of research in teacher education. Teacher emotions not only affect teachers themselves but also have an impact on their students. However, pre-service teachers’ emotions have been neglected. This study is based on a qualitative analysis of online emotional diaries related to emotional experience expression by 120 Chinese pre-service teachers before, during, and after teaching practice. The results in this study show three characteristics of pre-service teachers’ emotional experiences: the overall positive emotions are higher than negative emotions; “caring” and “nervous” are the most typical emotions and variability in emotional experience across gender and internship schools. Then, it is surprising that pre-service teachers’ emotional trajectories are complex and dynamic, positive emotions are decreasing, and negative emotions increase as time goes by. Finally, from the perspective of emotional experience sources, organizational factors affect the emotional experience, personal factors, and background factors.